Naive and Memory B Cell BCR Repertoires in Individuals Immunized with an Inactivated SARS-CoV-2 Vaccine - Renato Kaylan Alves de Oliveira França; Pedro Henrique Aragão Barros; Jacyelle Medeiros Silva; Hitallo Guilherme Costa Fontinele; Andrea Queiroz Maranhão; Marcelo de Macedo Brigido (Vaccines)
Background: The COVID-19 pandemic has spurred a global race for a preventive vaccine, with a few becoming available just one year after describing this novel coronavirus disease. Among these are inactivated virus vaccines like CoronaVac (Sinovac Biotech), which are used in several countries to reduce the pandemic’s effects. However, its use was associated with low protection, particularly against novel virus variants that quickly appeared in the following months. Vaccines play a crucial role in activating the immune system to combat infections, with Memory B-cells being a key part of this mechanism, eliciting protective neutralizing antibodies. This work focused on studying B-cell memory repertoire after two consecutive doses of CoronaVac. Methodology: Memory B-cells were isolated from five CoronaVac vaccinated and five pre-pandemic individuals and subsequently stimulated in vitro before high-throughput Illumina sequencing of the Heavy Chain Variable repertoire. Results: We observed a shift in the VH repertoire with increased HCDR3 length and enrichment of IGVH 3-23, 3-30, 3-7, 3-72, and 3-74 for IgA BCRs and IGHV 4-39 and 4-59 for IgG BCRs. A high expansion of IgA-specific clonal populations was observed in vaccinated individuals relative to pre-pandemic controls, accompanied by shared IgA variable heavy chain (VH) sequences among memory B cells across different vaccine recipients of IgA clones was also observed in vaccinated individuals compared to pre-pandemic controls, with several IgA VH sharing between memory B cells from different vaccines. Moreover, a high convergence was observed among vaccinees and SARS-CoV-2 neutralizing antibody sequences found in the CoV-abDab database. Conclusion: These data show the ability of CoronaVac to elicit antibodies with characteristics similar to those previously identified as neutralizing antibodies, supporting its protective efficacy. Furthermore, this analysis of the immunological repertoire in the context of viral infections reinforces the importance of immunization in generating convergent antibodies for the antiviral response.